Analysis of Challenges and Opportunities of Online Learning for Islamic Religious Education Teachers - Fitria Puji Atma Dewi; Zulfa Nisaul Fadlilah (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
The rapid growth of online learning in recent years has significantly influenced the teaching of Islamic Religious Education (IRE). This study analyzes the challenges and opportunities faced by Islamic Religious Education teachers in implementing online learning. The challenges include limited technological literacy among teachers and students, inadequate internet connectivity, lack of interactive media tailored to Islamic education, and difficulties in assessing students’ spiritual attitudes. Conversely, online learning provides opportunities for innovation in teaching methods, the development of digital-based Islamic learning resources, and the flexibility to integrate global Islamic knowledge through virtual platforms. This research highlights that addressing these challenges requires comprehensive training for teachers, improvement of digital infrastructure, and the development of pedagogically appropriate e-learning materials. Furthermore, the adoption of blended learning models is suggested to optimize both technology and the humanistic values of Islamic education. The findings of this study contribute to formulating effective strategies for enhancing the quality of Islamic Religious Education in the digital era.